148 Residual feed intake and body weight gain relate to feeding behavior in Nellore bulls: Implications for performance and maintenance requirements. (5th December 2019) - Menezes, Ana Clara B; Filho, Sebastião Valadares; Benedetti, Pedro; Pacheco, Marcos; Pucetti, Pauliane; Silva, Breno; Zanetti, Diego; Silva, Fabyano; Paulino, Mário; Chizzotti, Mário; Neville, Tammi; Caton, Joel
Abstract: This study determined feed intake behavior, performance, feed efficiency, and maintenance requirements of bulls with high and low residual feed intake and body weight gain. Data were collected from 42 weaned Nellore bulls (initial BW 260 ± 8.1 kg; age 7 ± 1.0 mo) housed in a feedlot in a group pen that contained electronic feeders. Individual dry matter intake (DMI) was recorded daily and body weight (BW) was measured every 28 d over a 140-day period. Indexes of average daily gain (ADG), feed efficiency, and residual feed intake (RFI) were calculated. Residual feed intake and gain (RFIG) was calculated according to previously published equations. Frequency of meals, duration per visit, and time spent feeding per day were recorded as feeding behavior measures. Maintenance requirements were calculated according to the BR-CORTE system. High RFIG bulls had lower DMI (P < 0.01), lower final BW (P < 0.01), and were more feed efficient (P < 0.01) than low RFIG bulls, but both groups had similar ADG (P = 0.55). No differences in feeding behavior were observed between the two groups (P > 0.05). The net energy requirements for maintenance, metabolizable energy for maintenance, and efficiency of metabolizable energy utilization were 76.5, 122.68 kcal/EBW 0.75 daily, and 62.4%, respectively for high RFIG bulls, and 89.2, 143.76 kcal/EBW 0.75 daily, and 62.0% for low RFIG bulls. This study reveals that low RFIG bulls are less feed efficient and have greater maintenance requirements than high RFIG bulls (0.16 ± 0.006 and 0.18 ± 0.006, respectively). As low RFIG eat more, and in beef cattle, feeding behavior is associated with methane emissions, we suggest further research evaluating this relationship be conducted. In addition, selection for high RFIG cattle would improve feed efficiency, reduce production costs, and could potentially reduce methane emissions.